Risk factors of respiratory effects from work exposure and PM2.5 among policeman - Mohamad Jamil, Putri Anis Syahira (2016)
Without any protections from traffic-related air pollution, traffic policeman was exposed to them on daily basis as their duties are to manage traffic congestion. This study was to determine the risk of respiratory effects from work exposure and PM2.5 among traffic policemen. A pulmonary function test using spirometer was used to measure pulmonary function of subjects and personal air sampling pumps were used to measure personal exposure level of PM2.5. In order to collect background data, occupational and health history, questionnaires were given to each subject. The mean exposure level of PM2.5 among traffic policemen was 28.69 μg/m3. The traffic policemen were determined as having lower lung function parameters (FVC, 91% and FEV1, 94%) due to their nature of work and the environment. It was found that some of them possess respiratory symptoms (Coughing 33.6%, Phlegm 25.4%, Wheezing 14.9% and 32.1%). From the finding, PM2.5 personal exposures level (p<0.05), age (p=0.04), rank (p=0.04), duration of services (p=0.01), and average working hours (p<0.001) were significantly related with pulmonary function among traffic police. Also, PM2.5 personal exposures level was significantly associated with coughing (p<0.05) among traffic policemen. The outcomes also indicated that the main factors of abnormality in lung functions are exposure to PM2.5 and duration of services. These baseline data can be used in the future studies by researcher, engineers and students. Most importantly, they serve as reference to the top management of traffic police officers in order to develop an occupational safety and health guideline for police officers as they are covered by Occupational Safety and Health Act (OSHA, Act 514 1994).